2018
DOI: 10.1016/j.celrep.2017.12.039
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Astrocyte Transcriptome from Multiple Regions of the Mouse Brain

Abstract: SUMMARY Aging brains undergo cognitive decline, associated with decreased neuronal synapse number and function and altered metabolism. Astrocytes regulate neuronal synapse formation and function in development and adulthood, but whether these properties change during aging, contributing to neuronal dysfunction, is unknown. We addressed this by generating aged and adult astrocyte transcriptomes from multiple mouse brain regions. These data provide a comprehensive RNA-seq database of adult and aged astrocyte gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
621
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 559 publications
(661 citation statements)
references
References 52 publications
40
621
0
Order By: Relevance
“…Thirty genes overlapped, including Gfap, Aqp4 (encoding the astrocytic water channel aquaporin-4), and Megf10 , a gene involved in astrocyte-mediated synaptic elimination (Chung et al, 2013). C4b , a complement cascade component also implicated in synapse elimination and a marker of astrocyte activation and aging (Boisvert et al, 2018; Clarke et al, 2018), was strongly upregulated (4-fold) in NBmal1 KO brain. Several other disease-associated astrocytic genes were increased in NBmal1 KO brain, including inflammatory mediators such as Cxcl5 and Ccr7 and the matrix metalloproteinases Mmp14 and Mmp2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty genes overlapped, including Gfap, Aqp4 (encoding the astrocytic water channel aquaporin-4), and Megf10 , a gene involved in astrocyte-mediated synaptic elimination (Chung et al, 2013). C4b , a complement cascade component also implicated in synapse elimination and a marker of astrocyte activation and aging (Boisvert et al, 2018; Clarke et al, 2018), was strongly upregulated (4-fold) in NBmal1 KO brain. Several other disease-associated astrocytic genes were increased in NBmal1 KO brain, including inflammatory mediators such as Cxcl5 and Ccr7 and the matrix metalloproteinases Mmp14 and Mmp2.…”
Section: Resultsmentioning
confidence: 99%
“…While Bmal1 -deficient astrocytes do not assume a clear neurotoxic (“A1”) phenotype, they are less able to support neuronal survival in a co-culture system and express numerous transcripts associated with inflammation and neurodegeneration. These include C4b , a complement component and marker of astrocyte activation and aging (Boisvert et al, 2018; Clarke et al, 2018), Megf10 , which mediates astrocytic synapse elimination (Chung et al, 2013), and Pla2g3 , a phospholipase implicated in ROS-induced neuronal damage (Martínez-García et al, 2010). Activation marker Lcn2 (lipocalin 2), an anti-inflammatory mediator in the brain (Kang et al, 2018), was not increased, again suggesting a pro-inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that there is significant heterogeneity in astrocytes across different brain regions. For example, hypothalamic astrocytes express more genes for lipid oxidation compared with cortical astrocytes, which express more genes for lipid synthesis [48]. Regional differences in astrocytic glycogen content also exist, with high levels in hippocampus and cortex and comparatively lower levels in subcortical structures [49].…”
Section: Discussionmentioning
confidence: 99%
“…These include the well-established antibodies against CD45 (36) and O4 (37,38), the astrocyte-specific anti-ACSA-2 antibody that has been recently validated by ourselves and independent groups (27,39,40), (Supplemental Figure 2), and the anti-CD49a antibody ( Figure 1B, Figure 2, and Supplemental Figure 2). Employing the commonly used ALDH1l1-EGFP reporter (41) believed to mark the majority of astrocytes, we found that the anti-ACSA-2 antibody labeled all GFP + astrocytes in addition to a sizable GFP -astrocyte population (Supplemental Figure 3A), suggesting that this reporter line does not mark all astrocytes in adult brains.…”
Section: Concurrent Brain Cell Type Acquisition From a Single Adult Mmentioning
confidence: 99%
“…In addition, multiple cell types have been isolated and profiled concurrently by using a combinatorial approach of reporter lines and/or multiple antibodies (1,5,6). RiboTagging has also been used in single cell types to investigate gene expression in actively translated mRNAs in neurons (25), microglia (26), and astrocytes (27). However, genetic reporter lines and RiboTagging are often intractable to disease models because they require complicated multiallele crosses.…”
Section: Introductionmentioning
confidence: 99%